Bontang City Physics Teachers' Understanding of Revised Bloom's Taxonomy Cognitive and Knowledge Dimensions in Physics Questions - Fitri, Muhammad Fauzan; Qadar, Riskan; Hakim, Abdul (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This study aims to determine the teacher's understanding of physics questions in revised Bloom taxonomy on optics. This type of research is descriptive quantitative research using survey method. The population of this study were Physics Subject Teachers in Bontang City. Sampling technique carried out using purposive sampling technique with criteria of teachers who teach Physics subjects for junior and senior high school. Data collection techniques were carried out using test and analyzed based on predetermined categories. The results obtained are the understanding of cognitive dimension of teacher is in the medium category with details of very high category 0%, high category 10%, medium category 47%, low category 30%, and very low category 13%. While in knowledge dimension, teachers' understanding is in the moderate category with details of very high category 3%, high category 7%, medium category 33%, low category 50%, and very low category 7%.